Antibacterial Effects of Compound Bifilact on E.coli and Campylobacter jejuni - Hamidreza Ebrahimnezhad; Leila Barzegar; Davoud Esmaeili (Medical Laboratory Journal, 2020)
ABSTRACT Background and Objectives: Probiotics are live microorganisms that function through  various mechanisms  and affect the alteration of the commensal microbiota against pathogens. Nowadays,  given the problems associated with antibiotics use, probiotic strains  offer a novel and  appropriate  alternative for the treatment of diseases such as diarrhea. The aim of this study was to investigate the antibacterial synergism of Lactobacillus spp., Bifidobacterium spp. and Escherichia coli strain Nissle 1917 (ECN) on the clinical sample of diarrheagenic E.coli and Campylobacter jejuni. Methods: A paper disk-diffusion technique was used to evaluate the antibacterial activity. Sterile 6 mm paper disks were saturated with probiotic suspensions made by settling probiotic medications into distilled water. Three kinds of disk were prepared. One disk was prepared for Lactobacillus spp. and Bifidobacterium spp., another for ECN, and the third was made by combined probiotics. Clinical samples of diarrheagenic E.coli and Campylobacter jejuni were cultivated on Muller Hinton agars, and disks were placed on the inoculated Muller Hinton agars. All plates were incubated under microaerophilic and appropriate conditions. Results: The zone of inhibition (ZOI) of the bacterial growth was measured. All pathogenic microorganisms showed sensitivity to the probiotic disks. The combined disks had better effects against pathogens compared with single disks. Conclusion: A considerable synergistic effect was observed in the results of combined probiotics; therefore, combined strains can be more efficient against intestinal pathogens in comparison with single probiotics. Keywords: Probiotic, Lactobacillus, Bifidobacterium, Escherichia coli Nissle, Diarrhea, Campylobacter jejun.i.